Umar Bin Abdul Aziz dan Semangat Penulisan Hadis - Saifuddin Zuhri Qudsy (UIN Sunan Kalijaga Yogyakarta, 2013)
Here I try to uncover various foundation of time and space underlying the nature of caliph ‘Umar bin ‘Abdul ‘Aziz’s thought who formally commanded codifying hadith. I use Peter L. Berger theory of sociology of knowledge to get an understanding of how the process ‘Umar bin ‘Abdul ‘Aziz that has lived in the luxuriousness dynastic of Umayyah capable to pay attention on hadith whereas formerly it was allowed running wild in the arms individual thalib hadith and didn’t get attention from any Umayyad caliphate.